ANALYSIS OF THE RATIONAL ORDER OF APPROXIMATION POLYNOMIA FOR RECOVERING INFORMATION BY ITS DISCRETE COUNTS - Moroz, V. I. (Radio Electronics, Computer Science, Control, 2024)
The rational polynomial approximation order of sampling signal reconstruction was analyzed using Bode plots.